Sunni dan Syiah dalam Perspektif Sejarah Awal Islam: Akar Teologis dan Dinamika Politik - Puspa Fitria Dewi; Nurlaelah Abbas; Mahmuddin M (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This article examines the emergence of Sunni and Shi‘a Islam within the context of early Islamic history by exploring their theological foundations and political dynamics. The division between the two traditions originated from debates over leadership succession following the death of the Prophet Muhammad, particularly concerning the legitimacy of authority and the nature of political and religious leadership. Sunni Islam conceptualized leadership as a matter of communal consensus grounded in pragmatic governance, whereas Shi‘a Islam developed the doctrine of imamate by viewing leadership as a divinely ordained institution vested in the family of the Prophet. Through a historical and analytical approach supported by qualitative literature review, this study traces how initial political disputes gradually evolved into distinct theological systems that shaped divergent doctrines, patterns of religious authority, and collective identities. The findings demonstrate that the Sunni and Shi‘a divide cannot be understood solely as a theological disagreement, but must be situated within broader historical processes involving power, legitimacy, and sociopolitical transformation. Understanding these historical roots is essential for fostering a more nuanced and constructive engagement with sectarian differences in contemporary Islamic discourse.